ESENSI JAMINAN FIDUSIA DAN RAHN DALAM PELAKSANAAN EKSEKUSI JAMINAN KEBENDAAN: THE ESSENCE OF FIDUCIARY COLLATERAL AND RAHN IN THE EXECUTION OF MATERIAL COLLATERAL - Andriyani, Gina; Alamudi, Ichwan Ahnaz (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The background of economic development in Indonesia includes sectors related to business activities carried out by business people who will always hold back the flow of developing consumptive needs by requiring guarantees to fulfiil the credit facilities provided. This paper discusses the problem in the form of collateral execution if the debtor defaults, both by law and Islamic law. This study used the library research method and used a normative appoarch with a juridical approach. Based on the results of this paper, it can be concluded that the implementation of the execution of fiduciary guarantees based on the fiduciary guarantees act, has a new perspective in its implementation and has similarities with rahn according to Islamic law which can be combined with rahn tasjily in material guarantees